Sistem Informasi Koperasi Simpan Pinjam pada PT Meiwa Indonesia Berbasis Java Desktop - Nurrohman Nurrohman; Meri Chrismes Aruan; Andri Rahadyan (Jurnal Informatika Universitas Pamulang, 2020)
This study aims to facilitate performance in the cooperative data storage and storage organization of PT MEIWA INDONESIA. The research method used by researchers is a research method that is based on fact-based research methods and uses comparative analysis with the aim of generating empirical, concept building, proving theories, developing theories, analyzing data and analyzing data. The results obtained are the idea of a savings and loan cooperative information system to assist in processing employee data. The development of an information system is expected to simplify and provide maximum service to employees and facilitate cooperative staff in collecting loan transaction data for reporting, making data and information management processes more effective, producing faster output and no loan requests, data input or data duplication.